Analisis Program Antar Jemput (Aji) Dalam Meningkatkan Pelayanan Administrasi Terpadu Kecamatan (Paten) Di Kecamatan Babulu Kabupaten Penajam Paser Utara - Ayu Ajeng Nurfadhillah (Jurnal Sosial-Politika, 2020)
The purpose of this study is to determine how the Antar Jemput Izin (AJI) is implemented by Babulu District in improving the Pelayanan Administrasi Terpadu Kecamatan (PATEN). Data collection techniques in this study were obtained using purposive sampling technique and accidental sampling. The data analysis used in this research is descriptive qualitative which aims to provide a description of each of the variables studied. The results showed that the analysis of the Antar Jemput Izin (AJI) program in improving the Pelayanan Administrasi Terpadu Kecamatan (PATEN) in Babulu District by looking at the transparency, accountability, conditional, participatory, and non-discriminatory system is running quite well.